Mapping Online Business and Grocery Research Trends - Amien, Muhammad Najmy; Phahlevy, Rifqi Ridlo; Fiddina, Irta (Proceedings of The ICECRS, 2023)
This data article presents a comprehensive dataset obtained from Lens.org, focusing on the intersection of "Online Business" and "Grocery." The data collection involved filtering for "Journal Articles" and "Conference Proceedings" with the "Law" subject matter. The primary objective was to quantify the volume of research on Online Business and Grocery using the keyword "online business AND grocery" on Lens.org. The dataset contains 3,522 relevant documents. Notably, the University of Technology Sydney, University of Melbourne, University of Bath, Northumbria University, and London School of Economics and Political Science are the top institutions contributing to this research domain, collectively generating 2 journal articles. The dataset spans a wide range of years, with 2016 and 2017 being the most prolific years, each yielding 8 journal articles. Sociology emerges as the dominant field, contributing 16 journal articles. The dataset's primary utility lies in aiding researchers seeking information related to the intersection of Online Business and Grocery, particularly within the legal context. Additionally, it serves as a valuable resource for scholars exploring trends in this domain. Highlight: Data Analysis: Comprehensive data analysis reveals cybersecurity trends, helping organizations adapt to evolving online threats. Research Insights: Deep insights from data highlight critical aspects of cybersecurity, informing proactive measures. Security Measures: Data-driven findings support the implementation of robust security measures to safeguard digital assets. Keywords: Data Analysis, Cybersecurity Trends, Online Threats, Research Insights, Security Measures